Digital Business Communication in Islamic Perspective on New Entrepreneurship in the Catering Service Sector - Wiwitan, Tresna; Yulianita, Neni; Yuningsih, Ani; Kurniadi, Oji; Subur Drajat, M. (KnE Social Sciences, 2023)
Business competition in the digital era causes traditional entrepreneurs to try to develop their businesses by utilizing and maximizing new patterns in building their businesses online. Many businesses use digital or online media to support their business development, for example, by displaying creative content in the form of advertising, publicity, advertorials, direct marketing, and others on social media platforms such as Facebook, Instagram, YouTube, Tiktok, and the other social media. This study on digital business communication was carried out on 14 students and members of the Ulul Albab Islamic Boarding School who participated in the new entrepreneurship development training in the field of catering through the use of social media as a business medium, in order to improve their competence. The descriptive method is used to assess the level of knowledge of the members following training. Data were collected using pre and post-test instruments, focus group discussions with three participants, interviews with administrators, and observations during the training. The results of measuring the effectiveness of the training revealed that it was successful in increasing the knowledge and skills of the participants, the Ulul Albab Islamic Boarding School students, in the areas of creative content, creative photos, digital business communication ethics, and business communication from an Islamic perspective. Social media is used in business, the content consists of food service products produced in Islamic boarding schools. Keywords: online media, online business, catering service sector, Pesantren